German ambassador in London. A few days before his death (April 10) while having a stroll during the sessions of the League of Nations Council in London. From: Keesings Wereldgebeuren in Beeld, 1936
German ambassador in London. A few days before his death (April 10) while having a stroll during the sessions of the League of Nations Council in London. From: Keesings Wereldgebeuren in Beeld, 1936.